Pengaruh Kepuasan Kerja dan Kompensasi Kerja terhadap Kinerja Karyawan CV. Karya Kita Mandiri - Ulfa Natsir; Ades Asike (Movere Journal, 2026)
The data collection techniques that researchers use in this study are observation, interviews, questionnaires, and documentation. As a population, all employees at CV. Karya Kita Mandiri. In order for this research to be precise and proportional, in this study saturated sampling was used where population members were sampled. Thus the number of samples in this study were 52 people. The results of this study indicate that (1) Job Satisfaction Variable (X1) has a partial effect on employee performance at CV. Karya Kita Mandiri with tcount> ttable (4.889> 2.008) and significant <0.05 (0.000 <0.05). (2) Compensation variable (X2) has no partial effect on employee performance at CV. Karya Kita Mandiri with the results of tcount < ttable (0.223 < 2.008) and significant > 0.05 (0.824 > 0.05). (3) Job Satisfaction and Compensation simultaneously affect employee performance at CV. Karya Kita Mandiri with Fcount> Ftable (31.162> 3.18) and significant <0.05 (0.000 <0.05). (4) The value of R2 = 0.564 means that the influence of the variables Job Satisfaction (X1) and Compensation (X2) on employee performance (Y) is 56%. While the remaining 44% is influenced by other variables not included in this study such as leadership style, work environment, work discipline, work motivation, etc.